Case study: energy availability and endocrine markers in elite male track cyclists - Schofield, K. L.; Thorpe, H.; Sims, S. T. (International Journal of Sports Physiology and Performance, 2022)
Aim: To highlight energy availability status, resting metabolic rate measures, dietary protein intake, and testosterone concentration in 4 elite male track cycling athletes (mean [SD]: age: 20.8 [1.5] y, body mass: 76.3 [3.6] kg, height: 181.8 [2.9] cm).